Analisis Faktor-faktor Yang Mempengaruhi Likuiditas Bank BNI Syariah dan Bank BCA Syariah - Muhammad Tho'in; Yuge Agung Heliawan (ITB AAS INDONESIA Surakarta, 2020)
The purpose of this research is to determine the analysis of the factors that affect the liquidity of Islamic banks at Bank BNI Syariah and Bank BCA Syariah in 2010-2018. This research uses descriptive quantitative research that uses secondary data sources in the form of financial reports. This research uses quantitative methods, where this method is used to test the hypothesis. Sources of data in this study are secondary data in the form of financial statements of Bank BNI Syariah and Bank BCA Syariah for 2010-2018 from the official website www.bnisyariah.co.id and www.bcasyariah.co.id which are supported by journals and reference books related to research, as well as other information related to this research. The population of this research is the financial statements of Bank BNI Syariah and Bank BCA Syariah in 2010-2018. The sampling technique used purposive sampling technique, the sample in this study was quarterly financial report data published for 9 consecutive years by Bank BNI Syariah and Bank BCA Syariah. The data used is secondary data from the official website www.bnisyariah.co.id and www.bcasyariah.co.id. The results showed that the CAR variable has a significant effect on Liquidity (FDR), the NPF variable has a significant effect on Liquidity (FDR), the TPF variable has no significant effect on Liquidity (FDR), simultaneously the CAR, NPF and TPF variables have a significant effect on Liquidity ( FDR).